An assessment of the effectiveness of a long-term ecosystem restoration project in a fynbos shrubland catchment in South Africa. (1st January 2017) - Fill, Jennifer M.; Forsyth, Greg G.; Kritzinger-Klopper, Suzaan; Le Maitre, David C.; van Wilgen, Brian W.
Abstract: The long-term effectiveness of ecological restoration projects is seldom reported in the scientific literature. This paper reports on the outcomes of ecosystem restoration following the clearing of alien Pinus plantations and associated alien plant invasions over 13 years from an 8000 ha mountain catchment in the Western Cape Province, South Africa. We examined the goals, methods and costs of management, and the ecological outcomes in terms of reduced alien plant cover and native vegetation recovery. While the goals were not explicitly formulated at the outset, they were implicitly focussed on the conservation of water resources, the restoration of biodiversity, and the provision of employment. Initially, most (>90% of the area) was occupied by Pinus and Acacia invasions, mostly at low densities. The cost of control (initial clearing and up to 16 follow-up visits to remove emergent seedlings) amounted to almost ZAR 50 million (14 ZAR ∼ 1US$). Although the cover of alien plants was greatly reduced, over 1000 ha still support dense or medium invasions (>25% cover), and the area occupied by scattered Pinus plants increased by over 3000 ha to >5700 ha. A reliance on passive restoration had not yet resulted in full recovery of the natural vegetation. The mean number of species, and total projected canopy cover on 50 m 2 plots was lower in cleared than in comparable reference sites with pristine vegetation (21 vs 32 species/plot, and 94 vs 168% cover respectively). While the project is ongoing, we conclude that the entire area could revert to a more densely-invaded state in the event of a reduction of funding. Several changes to the management approach (including the integrated use of fire, a greater use of power tools, and active re-seeding of cleared areas with indigenous shrubs) would substantially increase the future effectiveness of the project and the sustainability of its outcomes. Highlights: Effectiveness of long-term alien invasive plant clearing in South Africa was examined. Alien plant cover was reduced but scattered invasions remained extensive. Reliance on passive restoration had not yet resulted in full native vegetation recovery. Changes in the management approach are recommended.